2020
DOI: 10.1108/jbim-03-2019-0130
|View full text |Cite
|
Sign up to set email alerts
|

Market-scanning and market-shaping: why are firms blindsided by market-shaping acts?

Abstract: Purpose This paper aims to investigate two seminal market-scanning frameworks – the five-forces analysis and PESTEL environmental scanning tool – to assess their readiness for anticipating market-shaping acts. Design/methodology/approach Drawing on the market-shaping literature that conceptualizes markets as complex adaptive systems, this conceptual paper interrogates the underlying assumptions and “blind spots” in two seminal market-scanning frameworks. The paper showcases three illustrative vignettes in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Market research frameworks are not passive or innocent, but actively direct attention. For example, Diaz Ruiz et al (2020) investigated the ‘blind spots’ of strategic frameworks that prevent managers from noticing events until it is too late to react. Frameworks such as PESTLE or SWOT have underlying assumptions that shape mental models because they prioritise specific forces.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Market research frameworks are not passive or innocent, but actively direct attention. For example, Diaz Ruiz et al (2020) investigated the ‘blind spots’ of strategic frameworks that prevent managers from noticing events until it is too late to react. Frameworks such as PESTLE or SWOT have underlying assumptions that shape mental models because they prioritise specific forces.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Twenty years ago, research published in IJMR found that market researchers in the UK were aware that their commercial success depended upon providing usable information (Boddy, 2001), a finding that remains relevant (Nilsson, 2021). However, even though the use of judgement, sensibility, and strategic thought in market research is uncontroversial, an ongoing discussion debates whether market researchers tend to focus too much on the technical considerations for gathering and analysing descriptive data at the expense of strategising (Boddy & Croft, 2007; Diaz Ruiz et al, 2020; Piercy, 2006).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In particular, with regard to the intentionality discussion in market-shaping (Hawa et al, 2020), it becomes difficult to establish focal activities directing a market-shaping process. Relatedly, the fuzziness of market-shaping activities and their ambiguity with regards to cause-effect relationships may result in so-called "blind spots" (Diaz Ruiz et al, 2020, p. 1389. These blind spots occur due to either too broad or too narrow interpretations of what constitutes market change, thereby obscuring focal market actors' marketshaping efforts (Diaz Ruiz et al, 2020).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Relatedly, the fuzziness of market-shaping activities and their ambiguity with regards to cause-effect relationships may result in so-called "blind spots" (Diaz Ruiz et al, 2020, p. 1389. These blind spots occur due to either too broad or too narrow interpretations of what constitutes market change, thereby obscuring focal market actors' marketshaping efforts (Diaz Ruiz et al, 2020). By synthesizing a multitude of diverse theoretical and analytical lenses, our generalized activities mitigate potential blind spots by normalizing the extant empirical evidence.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The approach was summarized succinctly by Håkansson and Snehota (1989, p. 256) in the statement that “no business is an island.” The approach argues that firms that develop more and better network ties are likely to develop and mobilize more resources than less-connected firms (Lavie, 2006; Mitrega et al , 2012), in line with resource-dependence theory (Pfeffer and Salancik, 2003). According to Möller and Halinen (2017), the research streams on business networks cover the following five areas: the dynamics and capabilities of strategic networks (or nets) focusing on how firms can accomplish more by building interdependencies than by going alone (Ellis, 2010); the role of networks in enabling knowledge transfer, learning and co-creation (Araujo, 1998); how managers make sense of their position in the network, including modeling or picturing business network (Abrahamsen et al , 2016; Diaz Ruiz et al , 2020); the relevance of innovation networks in enhancing incremental or radical innovation (Freytag and Young, 2014); and finally an institutional approach to networks (Cheah, 2020), focusing on how groups of actors engage in collaboration and legitimization.…”
Section: Theoretical Backgroundmentioning
confidence: 99%